2014
DOI: 10.1002/2014je004692
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of explosive volcanism on Mercury: Implications from its global distribution and morphology

Abstract: The identification of widespread pyroclastic vents and deposits on Mercury has important implications for the planet's bulk volatile content and thermal evolution. However, the significance of pyroclastic volcanism for Mercury depends on the mechanisms by which the eruptions occurred. Using images acquired by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging spacecraft, we have identified 150 sites where endogenic pits are surrounded by a relatively bright and red diffuse-edged spectral anomaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 61 publications
(112 reference statements)
7
90
0
Order By: Relevance
“…This finding is in agreement with (Brož et al, 2015;Wilson & Head, 2003) and also with the observations of large faculae (up to 260 km in diameter) surrounding putative volcanic vents on Mercury, which show little (<1°) or no topographic relief at all (Thomas et al, 2014a). For a fixed eruption volume, wider dispersal necessarily leads to a decrease in the height of the final shape and to proportionately shallower flank slopes.…”
Section: The Shapes Of Pyroclastic Volcanoes On Airless Bodiessupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with (Brož et al, 2015;Wilson & Head, 2003) and also with the observations of large faculae (up to 260 km in diameter) surrounding putative volcanic vents on Mercury, which show little (<1°) or no topographic relief at all (Thomas et al, 2014a). For a fixed eruption volume, wider dispersal necessarily leads to a decrease in the height of the final shape and to proportionately shallower flank slopes.…”
Section: The Shapes Of Pyroclastic Volcanoes On Airless Bodiessupporting
confidence: 91%
“…The lower limit was chosen to resemble the typical volume of terrestrial scoria cones (determined from 986 edifices based on data from Pike, 1978, andHasenaka &Carmichael, 1985), and the upper limit of 40 km 3 was chosen as this is the median volume of putative large-scale explosive vents on the surface of Mercury (Thomas et al, 2014a). We chose volumes from 0.046 up to 40 km 3 with intermediate steps of 2.1, 4.2, 10, 20, and 30 km 3 .…”
Section: The Shapes Of Pyroclastic Volcanoes On Airless Bodiesmentioning
confidence: 99%
“…Peak ring crests were mapped as linear features where observed. Volcanic vents (rimless and irregular depressions, endogenic pits) were mapped integrating previous catalogs (Denevi et al, 2013;Thomas, Rothery, Conway, & Anand, 2014b). Thrust faults have been mapped using the triangular symbol located on the hangingwall while the graben symbology indicates only the trace of the structure.…”
Section: Methodsmentioning
confidence: 99%
“…The first hypothesis is consistent with the absence of spectral evidence for sulfide minerals in surface rocks (McClintock et al, 2008;Izenberg et al, 2014) while the second could explain the correlations between S and Ca-Mg observed in Mercurian lavas . Understanding the origin of high sulfur concentrations at the surface of Mercury is important to better constrain the structure of the planet and the distribution of sulfur amongst the different reservoirs (mantle, core and crust), the mechanisms of explosive volcanism (Kerber et al, 2009;Thomas et al, 2014a;Weider et al, 2016), and the formation of the hollows (sub-kilometer scale shallow depressions surrounded by bright deposits) which may have formed during sublimation of volatiles (Blewett et al, 2013;Thomas et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%